The Role of Parents in Shaping Children's Positive Behavior in RT 01 Muara Badak Ulu Village, Muara Badak District, Kutai Kartanegara Regency, East Kalimantan Province - Trisna Waty Riza Eryani; Kristina (PT FORMOSA CENDEKIA GLOBAL, 2023)
Parents have a very important role in the development of children. Children who are responsible and have positive behavior cannot be separated from their parents' parenting style. Sometimes there are still many children who have deviant behavior. The purpose of community service is to socialize the role of parents in shaping children's positive behavior. Methods of community service namely lectures and discussions. The results of the socialization activities went well, and 20 participants consisting of parents at rt 01 Muara Badak Ulu Village, Muara Badak District were very enthusiastic about participating in this activity because it can increase knowledge about how to shape children's behavior to be more positive.